Förderungen im Vergleich: Die inverse Subvention als effizientere Alternative - Dertwinkel-Kalt Markus; Wey Christian (Wirtschaftsdienst, 2025)
– Subsidies are a key economic policy instrument. This article analyses the effects of three types of subsidies. Ad valorem subsidies, in which the subsidy is granted in proportion to the price of the subsidised good, are particularly widespread. Although these subsidies stimulate demand, they lead to price-driving effects with limited volume expansion in markets with imperfect competition. In such realistic market forms, inverse subsidies, whose amount increases as the market price falls, offer a more efficient expansion of quantities at moderate costs. However, they remain underrepresented due to political and economic inertia and communicative complexity.
Keywords: D04; L11; L50; 330